Analysis of Conversational Implicature in Burnt Movie Directed by John Wells - Silvana Hamsah; La Aso; Ela Martisa (ELITE: Journal of English Language and Literature, 2022)
The objective of this research is to identify and describe the use of conversational implicature in the Burnt movie. The researcher used the implicature theory by Paul Grice to analyze the conversational implicature. The research methodology used in this research is a qualitative descriptive method. The source of this research is the data from the Burnt movie. To collect data, the researcher used several steps: watching the movie, pausing the movie that has conversational implicature, annotating the data, screenshotting the data, coding the data, and lastly reducing the data to present the needed data only. The result shows that both generalized and particularized conversational implicature is identified with the flouting maxim and the utterance that flouts the maxim has speech function. The use of conversational implicature in the character's utterances is such as useful for conducting good communication in the workplace. The characters use conversational implicature to convey the intention conveyed politely and quickly.